Pilot outcome results of culturally adapted evidence-based substance use disorder treatment with a Southwest Tribe - Kamilla L. Venner; Brenna L. Greenfield; Kylee J. Hagler; Jeremiah Simmons; Donna Lupee; Everett Homer; Yvette Yamutewa; Jane Ellen Smith (Addictive Behaviors Reports, 2016)
Introduction: Although American Indians/Alaska Natives (AI/ANs) have exhibited high rates of alcohol and drug use disorders, there is a paucity of substance use disorder treatment outcome research. In addition, there exists controversy about whether evidence-based treatments (EBTs) are culturally appropriate given that they were derived mainly by and for non-Hispanic White populations and do not explicitly include aspects of AI/AN culture and worldview. Methods: In this pilot study, we collaboratively culturally adapted two EBTs, Motivational Interviewing and Community Reinforcement Approach (MICRA), and evaluated substance use and psychological outcomes at 4- and 8-months post-baseline assessment. In preparation for a larger randomized clinical trial (RCT), eight tribal members (75% male) participated in this pilot treatment study. Measures included substance use, urine screens, self-efficacy, psychological distress, and hopelessness. All participants completed follow-up assessments at 4- and 8-months. Due to small sample size, effect sizes were calculated to evaluate outcomes pre- and post-treatment. Results: Despite high rates of abstinence at baseline, percent days abstinent (PDA) increased at the 8-month time point for the most commonly used substances (alcohol, Hedges's g = 0.59, and marijuana, g = 0.60) and for all substances combined (excluding tobacco, g = 0.56). Improvements in psychological distress (g = −0.66) and 5 of the 7 Addiction Severity Index domains (range of g = −0.42 to −0.98) also emerged. Conclusions: Results suggest that culturally adapted EBTs yield significant improvements in alcohol use, psychological distress, and legal problems among AI/ANs. Future research using RCT methodology is needed to examine efficacy and effectiveness.